(untitled) (Research, Society and Development, 2020)
Water, as a precious and necessary natural resource for the human existence, is subject of frequent study in laboratories all over the world. In the northeast of Brazil, specifically in the rural area, the water consumed by the communities usually comes from the rains and is stored in cisterns. A quality potability assessment of that water is necessary for human consumption. The water potability standards are regulated by Ordinance 2,914 / 2011 of the Ministry of Health. Consumption of water with quality indicators outside the parameters established by law can lead to diseases such as diarrhea, cholera, hepatitis, among others. In this context, the objective of this work was to characterize the waters of the cisterns as well as the potability patterns of these waters. Observed that the microbiological parameters were inappropriate for human consumption, since 88% of the samples presented microbiological contamination with the presence of Escherichia coli and only 12% of the total of cisterns analyzed showed adequate quality for potability.